Conjectures about a well-known problematic case: Old Prussian Ench. 89,2 arrien|tlāku (or Bezzenberger’s hypothesis revisited) - Dini, Pietro U. (Baltistica, 2024)
The aim of this article is to analyse both the linguistic and the hermeneutical question – as broadly conceived as possible – as well as the procedure followed in the earliest Baltic versions of Martin Luther’s Small Catechism. I discuss a difficult passage in the translation of the Small Catechism – namely Ench. 89,1–2: arrien|tlāku – in more detail, i.e. a case which many Prutenists have already interpreted in various ways but have failed to explain definitively or convincingly. I seek to present and critically discuss old and new conjectures, including the neglected proposal by Adalbert Bezzenberger.